Evidance Based Practice Terapi Senam Otak dengan Demensia di Panti Werdha Damai Ranomuut - Legi, Julita; Masengi, Christiachika Vanessa Roseline (JURNAL ILMIAH KESEHATAN MANADO, 2025)
Dementia is a disease of the brain organs and usually this disease is progressive and chronic. One of the cognitive stimulation therapies used to overcome dementia is brain exercises, where brain exercises are one of the interventions that can be used to improve the cognitive function of a person with dementia. The results of this study with the application of evidence based nursing brain gymnastics were carried out for 3 days, the results of the evaluation were found that brain gymnastics was effective in improving cognitive function in Mrs. M. L from a score of 13 increased to 21. Conclusion: This scientific paper has an improvement in cognitive function in Mrs. M. L with dementia who experiences memory impairment after being given brain exercises. Advice: to all health workers to be able to provide action and education on the application of brain exercises to clients with dementia.